2014
DOI: 10.1007/s12639-014-0600-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effect of Allium sativum on serum nitric oxide level and hepatic histopathology in experimental cystic echinococcosis in mice

Abstract: The current study was carried out to evaluate the prophylactic and therapeutic effects of Allium sativum on experimental cystic echinococcosis by measuring the serum nitric oxide level and studying hepatic histopathological changes. The experimental animals were divided into five groups, ten mice in each, group (I): prophylactic; group (II): therapeutic; group (III): prophylactic and therapeutic; group (IV): infected nontreated; group (V): non infected non treated. The results showed that serum nitric oxide wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Surgery is the method of choice for treating hydatid disease [19]. However, one study [10] reported that albendazole resulted in successful treatment in 49.3% of patients, partially successful treatment in 13.1%, improvement in 5.9%, and failure in 31.5% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is the method of choice for treating hydatid disease [19]. However, one study [10] reported that albendazole resulted in successful treatment in 49.3% of patients, partially successful treatment in 13.1%, improvement in 5.9%, and failure in 31.5% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The Griess reaction is based on two steps of diazotization reaction in which acidified NO2 -produces a nitrosating agent that reacts with sulfanilic acid to produce the diazonium ion. This ion is then coupled to N-(1-naphthyl) ethylenediamine to form the chromophoric azo-derivative which absorbs light at 540-570 nm according to nitric oxide assay kit (colorimetric) [21] at www.abcam.com (Version 7b Last Updated 9 August 2017).…”
Section: Assessment Of Drugs Efficacy Estimation Of Nomentioning
confidence: 99%
“…In recent years, garlic functional ingredients have become a hot topic in the research of medical research institutions in many countries [1][2][3]. In developed countries such as the United States, garlic pharmaceutical products tend to replace antibiotic products [4][5][6]. China is the world's largest garlic grower, accounting for more than 60% of the world's sown area and about 70% of the world's output.…”
Section: Introductionmentioning
confidence: 99%